\[\sum_{n=1}^{\infty} \dfrac{\ln(n)}{n^2} = \dfrac{\pi^2}{6}\left(12\ln(A) - \gamma - \ln(2\pi) \right)\]

Just for fun, I entered the above sum into WolframAlpha, and that's the answer it gave me. But I'm curious how we can actually prove that the sum has this closed form. Any ideas or solutions would be appreciated.

**Clarifications:**

\(A\) is the Glaisher-Kinkelin constant: \[A = \lim_{n\to\infty} \dfrac{e^{n^2/4}}{n^{n^2/2+n/2+1/12}}\prod_{k=1}^{n} k^k\]

\(\gamma\) is the Euler-Mascheroni constant: \[\gamma = \sum_{n=1}^{\infty} \left(\dfrac{1}{n} - \ln\left(1 + \dfrac{1}{n} \right) \right)\]

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestThe given sum also equals \(-\zeta^{'}(2)\)

In general, \[\sum_{n=1}^{\infty} \dfrac{\ln^{a}(n)}{n^b}=(-1)^{a}\zeta^{(a)}(b)\]

where \(\zeta^{(x)}(y)\) is the \(x^{th}\) derivative of Riemann Zeta function at \(y\).

Log in to reply